Spatiotemporal variation in ocean current driven hatchling dispersion: implications for the world’s largest leatherback sea turtle nesting region - Scott, R; Biastoch, A; Agamboue, PD; Bayer, T; Boussamba, FI; Formia, A; Godley, BJ; Mabert, BDK; Manfoumbi, JC; Schwarzkopf, FU; Sounguet, GP; Wagner, P; et al. (Diversity and Distributions, 2017)
This is the author accepted manuscript. The final version is available from the publisher via the DOI in this record. The lives of juvenile leatherback turtles are amongst the most enigmatic of all marine mega-vertebrates. For these widely dispersing cryptic organisms ocean models provide important insights into their likely dispersion from natal sites. Here, corroborated by fisheries bycatch data, we simulate spatiotemporal variation in hatchling dispersion patterns over five decades from within the World’s largest leatherback sea turtle nesting rookery (Gabon) and neighbouring rookeries to the north (Gulf of Guinea) and south (the Republic/Democratic Republic of the Congo) of the equator (3.5°N-6°S). Due to the dynamism of oceanic conditions at these equatorial latitudes dispersion scenarios differed significantly: (1) along the north to south gradient of the study region, (2) seasonally and (3) between years. From rookeries to the north of the equator, simulated hatchling retention rates within the Gulf of Guinea were very high (>99%) after 6 months of drift whilst south of the equator, retention rates were as low as ~6% with the majority of simulated hatchlings dispersing west into the South Atlantic Ocean with the South Equatorial Current. Seasonal dispersion variability was driven by wind changes arising from the yearly north/south-ward migration of the intertropical convergence zone resulting in the increasing westerly dispersion of hatchlings throughout the hatching season. Annual variability in wind-stress drove a long term trend for decreased retention within the Gulf of Guinea and increased westerly dispersion into habitats in the South Atlantic Ocean. Shifts in dispersion habitats arising from spatiotemporal oceanic variability exposes hatchlings to different environments and threats that will influence important life history attributes such as juvenile growth/survival rates; anticipated to impact the population dynamics and size/age structure of populations into adulthood. The impacts of local ...